2005
DOI: 10.1186/1478-1336-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary selection across the nuclear hormone receptor superfamily with a focus on the NR1I subfamily (vitamin D, pregnane X, and constitutive androstane receptors)

Abstract: BackgroundThe nuclear hormone receptor (NR) superfamily complement in humans is composed of 48 genes with diverse roles in metabolic homeostasis, development, and detoxification. In general, NRs are strongly conserved between vertebrate species, and few examples of molecular adaptation (positive selection) within this superfamily have been demonstrated. Previous studies utilizing two-species comparisons reveal strong purifying (negative) selection of most NR genes, with two possible exceptions being the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 91 publications
(139 reference statements)
9
53
0
Order By: Relevance
“…Overall, the LBDs of PXR and CAR have sub-populations of codons with the highest ω ratios of any genes in the vertebrate NR superfamily [66,91]. These results strongly suggest that natural selection has favored sequence diversity in the LBD of PXR and CAR, possibly to adapt to cross-species differences in important ligands.…”
Section: Unusual Sequence Diversity Of Pxr and Car Genes Across Speciesmentioning
confidence: 86%
See 3 more Smart Citations
“…Overall, the LBDs of PXR and CAR have sub-populations of codons with the highest ω ratios of any genes in the vertebrate NR superfamily [66,91]. These results strongly suggest that natural selection has favored sequence diversity in the LBD of PXR and CAR, possibly to adapt to cross-species differences in important ligands.…”
Section: Unusual Sequence Diversity Of Pxr and Car Genes Across Speciesmentioning
confidence: 86%
“…Not surprisingly, a study comparing human, mouse, and rat and another study comparing human, mouse, and chimpanzee revealed that genes in the NR superfamily are tightly conserved across vertebrate species and hence have likely been subjected to negative evolutionary selection [1,90]. The only two clear exceptions are the LBDs of PXR and CAR [1,66,91].…”
Section: Unusual Sequence Diversity Of Pxr and Car Genes Across Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Krasowski and colleagues recently sug- gested that endogenous bile acids may have been the original ligands that drove PXR's evolution and species-specific variability [25]. Indeed, several groups have shown that PXR plays a crucial role in detecting the build-up of potentially toxic bile acids and up-regulating the expression of bile acid metabolizing enzymes to protect the liver and other tissues (see below).…”
Section: Ligand Bindingmentioning
confidence: 97%